Flavonoids from Pterogyne nitens Inhibit Hepatitis C Virus Entry. Issue 1 (December 2017) - Shimizu, Jacqueline; Lima, Caroline; Pereira, Carina; Bittar, Cintia; Batista, Mariana; Nazaré, Ana; Polaquini, Carlos; Zothner, Carsten; Harris, Mark; Rahal, Paula; Regasini, Luis; Jardim, Ana
Abstract Hepatitis C virus (HCV) is one of the leading causes of liver diseases and transplantation worldwide. The current available therapy for HCV infection is based on interferon-α, ribavirin and the new direct-acting antivirals (DAAs), such as NS3 protease and NS5B polymerase inhibitors. However, the high costs of drug design, severe side effects and HCV resistance presented by the existing treatments demonstrate the need for developing more efficient anti-HCV agents. This study aimed to evaluate the antiviral effects of sorbifolin (1 ) and pedalitin (2 ), two flavonoids fromPterogyne nitens on the HCV replication cycle. These compounds were investigated for their anti-HCV activities using genotype 2a JFH-1 subgenomic replicons and infectious virus systems. Flavonoids1 and2 inhibited virus entry up to 45.0% and 78.7% respectively at non-cytotoxic concentrations. The mechanism of the flavonoid2 block to virus entry was demonstrated to be by both the direct action on virus particles and the interference on the host cells. Alternatively, the flavonoid1 activity was restricted to its virucidal effect. Additionally, no inhibitory effects on HCV replication and release were observed by treating cells with these flavonoids. These data are the first description of1 and2 possessingin vitro anti-HCV activity.